Benzonaphthothiophene migration tracer: Selective separation and comparison with nitrogen tracers. (January 2022) - Arouri, Khaled R.; Panda, Saroj K.
Abstract: Benzonaphthothiophene (BNT) ratio (benzonaphtho[2, 1- d ]thiophene/benzonaphtho[1, 2- d ]thiophene) for five oil fields in Saudi Arabia, was measured and integrated with benzocarbazole ratio (BCR, benzo[ a ]carbazole/benzo[ c ]carbazole) and other geochemical data to track migration pathways and reduce charge risk. To improve analytical resolution, the sulfur-containing heterocycles were separated from the aromatic hydrocarbons using palladium(II)-bonded silica column prior to gas chromatography–mass spectrometry. The API gravity varies from 34.6° in the northernmost deepest field A to 14.7° in field E located 5000 ft (1524 m) shallower and 150 km to the south. This southward-shallowing trend is accompanied by a drop in the BNT ratio from 5.49 (field A) to 1.89 (field E). A common source kitchen and a narrow maturity range (0.78–0.84% calculated vitrinite reflectance), together with the lack of any evidence for biodegradation, collectively suggest that the observed fluid property variations in this petroleum system are controlled mainly by geochromatographic fractionation during migration. This is further attested by similarly decreasing BCR from 1.09 to 0.24, in agreement with southward migration. In comparison with the BCR, the BNT ratio shows wider variations with depth and relative migration distances, attesting to its value in tracking migration and reducing charge risk, especially in fluids that lack carbazole derivatives. Highlights: Benzonaphthothiophene (BNT) ratio compares well with benzocarbazole ratio for tracking migration across five oil fields. Palladium(II)-bonded silica column prior to gas chromatography–mass spectrometry improved analytical resolution. Migration fractionation explains API gravity variations for single-sourced unaltered fluids of quite similar maturity. BNT ratio is useful to map fluid movement and reduce charge risk, especially in systems that lack carbazole derivatives.